Solitary ulnar shortening osteotomy for malunion of distal radius fractures: experience of a centre in the UK and review of the literature - Hassan, S (Ann R Coll Surg Engl, 2019)
INTRODUCTION: Isolated ulnar shortening osteotomies can be used to treat ulnocarpal abutment secondary to radial shortening following distal radius fractures. Given the increase of fragility distal radius fractures awareness of treating the sequelae of distal radius fractures is important. We present the largest reported case series in the UK of ulnar shortening osteotomies for this indication. MATERIALS AND METHODS: Twenty patients with previous distal radial fractures were included, who presented with wrist pain and radiologically evident positive ulnar variance secondary to malunion of the distal radius with no significant intercalated instability. Patients were treated with a short oblique ulnar shortening osteotomy, using a Stanley jig and small AO compression plate system. Pre- and postoperative radiographical measurements of inclination, dorsal/volar angulation and ulnar variance were made. Patients were scored pre- and postoperatively using the Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) and Patient-Rated Wrist Evaluation scores by two orthopaedic surgeons. Mean follow-up was 24 months after surgery. RESULTS: Radiographical analysis revealed a change in the ulnar variance with an average reduction of 5.74 mm. Mean preoperative scores were 61.1 (range 25–95.5) for QuickDASH and 70.4 (range 33–92) for Patient-Rated Wrist Evaluation. At the latest follow-up, mean postoperative QuickDASH scores were 10.6 (range 0–43.2) and 17.2 (range 0–44) for Patient-Rated Wrist Evaluation. Differences in scores after surgery for both QuickDASH and Patient-Rated Wrist Evaluation were statistically significant (P < 0.01). CONCLUSIONS: The ulnar shortening osteotomy is a relatively simple procedure compared with corrective radial osteotomy, with a lower complication profile. In our series, patients showed significant improvement in pain and function by correcting the ulnar variance thus preventing ulna–carpal impaction.